Improved synthesis of perfluorooctylpropyl amine - Abulikemu, Abudurexiti; Halász, Gábor; Csámpai, Antal; Gömöry, Ágnes; Rábai, József (Journal of fluorine chemistry, 2004)
Graphic Hydrazinolysis of N-perfluorooctylpropyl phthalimide is an easy route to scale up for the title compound. Both the alkylation of potassium phthalimide with perfluorooctylpropyl iodide and the hydrogenolysis of the adduct of perfluoroctyl iodide to N-allyl-phthalimide provide this amine precursor in good yields. The latter procedure, however, has a better atom economy, since it requires only three steps from perfluorooctyl iodide.